Risk management in the shadow economy: Evidence from the sport betting market - Arscott, Robert (Journal of Corporate Finance, 2022)
I use the market for college football point spread gambling as a laboratory for assessing risk management activity among illegal firms. Offshore bookmakers employ pricing policies that reflect a book balancing objective whereas legal bookmakers seldom do so. Pricing policies that prioritize book balance lower the variance of bookmakers’ expected cash flow, but at the cost of lower profit. Due to the legal and moral hazards involved in operating an illegal enterprise, these firms rely on internal financing. Consequently, illegal bookmakers behave as mean–variance optimizers as opposed to legal bookmakers who appear to behave as profit maximizers.